1973
DOI: 10.1073/pnas.70.6.1708
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Snake α-Neurotoxin on the Development of Innervated Skeletal Muscles in Chick Embryo

Abstract: The evolution of the cholinergic (nicotinic) receptor in chick muscles is monitored during embryonic development with a tritiated a-neurotoxin from Naja nigricollis and compared with the appearance of acetylcholinesterase. The specific activity of these two proteins reaches a maximum around the 12th day of incubation. By contrast, choline acetyltransferase reaches an early maximum of specific activity around the 7th day of development, and later continuously increases until hatching. Injection of a-toxin in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
25
0

Year Published

1974
1974
1987
1987

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(33 citation statements)
references
References 35 publications
8
25
0
Order By: Relevance
“…1B and 4). This value closely agrees with levels of receptor reported for embryonic chick muscle in culture (3) and in ovo (17) and is comparable to the amounts of receptor per mg of protein in electrolplax of electric eel, estimated by affinity labeling (19).…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…1B and 4). This value closely agrees with levels of receptor reported for embryonic chick muscle in culture (3) and in ovo (17) and is comparable to the amounts of receptor per mg of protein in electrolplax of electric eel, estimated by affinity labeling (19).…”
Section: Discussionsupporting
confidence: 79%
“…Cholinesterase activity was demonstrated in avian muscle by Nachmansohn (16), and this activity has been recently reported to increase in parallel with receptor in embryonic chick muscle during development in ovo (17). The rapid kinetics shown by the chick muscle cultures with respect to cell fusion 3208…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that, while clustering of AChRs at the nervemuscle contact does not depend on muscle activity, the loss of multi-endplate status and accumulation of AChE may depend on muscle activity (Giacobini et al, 1973;Lomo and Slater, 1978;Rubin et al, 1980;and review in Bennett, 1983). Development of organized neuromuscular junctions in the rat has also been considered to be linked to muscle activity (Lomo et al, 1984).…”
Section: Discussionmentioning
confidence: 99%